Depression in Danish and Swedish elite football players and its relation to perfectionism and anxiety. (May 2018) - Jensen, Stine Nylandsted; Ivarsson, Andreas; Fallby, Johan; Dankers, Silke; Elbe, Anne-Marie
Abstract: Objectives: The aim of this study was to investigate the relation of perfectionism and anxiety to depressive symptoms in Danish and Swedish male elite football players. Additionally, the relationship between age and the study variables, and differences between elite junior and professional players were examined. Design and Methods. A cross-sectional design was used to survey 323 A-squad and U19 players (M age = 22.08 years, SD = 5.15). The survey included biographical information as well as measures of depressive symptoms, perfectionism (strivings and concerns), competitive anxiety, and social phobia. Results. Results revealed an overall prevalence rate for depressive symptoms among the participants of 16.7%. Moreover, correlation analyses showed evidence of the relationships between depression and perfectionistic concerns, competitive anxiety and social phobia. The results of a mediation analysis demonstrated that there was a positive indirect effect of perfectionistic concerns on depression via competitive anxiety. Significant negative correlations between age and anxiety, social phobia, and perfectionistic concerns were found. Depression, however, was not significantly correlated with age even though elite junior players' depression levels were significantly higher than those of professional players and they showed higher levels in competitive anxiety and social phobia. Conclusions. Findings of the study indicate that more awareness of mental health in elite football is needed, and that the investigated psychological factors may be a starting point for establishing preventive programs and supportive interventions for footballers suffering from depressive symptoms. Highlights: 16.7% of elite Danish and Swedish footballers showed depressive symptoms. Depressive symptoms were related to perfectionistic concerns, competitive anxiety and social phobia. Age was negatively related to anxiety, social phobia, and perfectionistic concerns. Elite junior players reported higher levels of depression than professional players. More awareness of mental health in elite football is needed.